1990
DOI: 10.1093/carcin/11.6.1005
|View full text |Cite
|
Sign up to set email alerts
|

Tissue distribution of DNA adducts in CDF1 mice fed 2-amino-3-methylimidazo[4,5-f]quinoline (IQ) and 2-amino-3,4-dimethylimidazo[4,5-fquinoline (MeIQ)

Abstract: Male and female CDF1 mice were administered a single oral dose of 3 mumol of the food mutagens 2-amino-3-methylimidazo[4,5-f]quinoline (IQ) or 2-amino-3,4-dimethylimidazo[4,5-f]quinoline (MeIQ) and killed 24 h later. DNA was isolated from the livers, lungs, kidneys, colon and forestomach and analysed by 32P-postlabelling for the presence of IQ and MeIQ adducts. Several adduct-enrichment procedures were investigated, including ATP-deficient labelling conditions, butanol extraction and nuclease P1 digestion, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The chromatographic analysis of the adducts formed in vivo was performed on a PEI-cellulose sheet as described in Materials and Methods. The contact transfer method performed on an RP18 TLC sheet ( ) was used, in addition, to minimize the radioactive background on the TLC sheet, in particular, in the region where the adduct spot appears at the PEI-cellulose sheet and to avoid artifacts. Information about the reproducibility of the contact transfer method is actually rather scarce in the literature ( ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The chromatographic analysis of the adducts formed in vivo was performed on a PEI-cellulose sheet as described in Materials and Methods. The contact transfer method performed on an RP18 TLC sheet ( ) was used, in addition, to minimize the radioactive background on the TLC sheet, in particular, in the region where the adduct spot appears at the PEI-cellulose sheet and to avoid artifacts. Information about the reproducibility of the contact transfer method is actually rather scarce in the literature ( ).…”
Section: Resultsmentioning
confidence: 99%
“…The contact transfer method performed on an RP18 TLC sheet ( ) was used, in addition, to minimize the radioactive background on the TLC sheet, in particular, in the region where the adduct spot appears at the PEI-cellulose sheet and to avoid artifacts. Information about the reproducibility of the contact transfer method is actually rather scarce in the literature ( ). We found a relative standard deviation of 27%.…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies have been reported on HAA-DNA adduct formation and 32P-postlabeling analysis (17,19,22,(24)(25)(26)(27)(32)(33)(34)(35). There is considerable interlaboratory variation in the DNA adduct profiles, which appear quite complicated in many instances.…”
Section: Discussionmentioning
confidence: 99%
“…It was concluded that the dG-N 2 -IQ adduct is not detected when labeling under adduct intensification conditions and that adduct enrichment before postlabeling is necessary for quantitative labeling of IQ-DNA adducts (30). Adduct enrichment by nuclease P1 (38) or butanol extraction (34) has been suggested to be unsuitable for some heterocyclic amine DNA adducts (21). In a few cases, however, the butanol extraction assay and/ or the nuclease P1 assay have been used for adduct enrichment of heterocyclic amine DNA adducts (18,39,40).…”
Section: Discussionmentioning
confidence: 99%
“…32 P-Postlabeling is a very sensitive technique which can detect DNA adducts in the range of 1 adduct per 10 7 -10 10 nucleotides in a 10 µg DNA sample. The ATP-deficient version of the 32 P-postlabeling assay followed by chromatographic separation by 32 P-TLC has been extensively used for analysis of DNA adducts formed by several different food mutagens in vitro as well as in rodents and monkeys (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). However, in order to detect all DNA adducts in a sample, it is necessary to perform 32 P-postlabeling with an excess of [ 32 P]ATP (30).…”
Section: Introductionmentioning
confidence: 99%